Secondary battery and device
By using carbon-based materials in the negative electrode sheet of the secondary battery and controlling its surface defect growth rate, the problem that fast-charge graphite negative electrodes are difficult to take into account high-energy fast charging, long cycles and high-temperature storage is solved, and high energy density, fast charging capabilities and cycle stability are improved.
Patent Information
- Application Number
- CN202311178016.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, due to the large surface defects of the fast charging graphite negative electrode, it is difficult to take into account high energy fast charging, long cycles and excellent high-temperature storage characteristics.
A secondary battery is provided, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes a carbon-based material, and the surface defect growth rate of the carbon-based material is controlled from 5% to 25%.
By controlling the surface defect degree and growth rate of the negative electrode sheet, the high-energy fast charging, long cycle and excellent high-temperature storage characteristics of lithium-ion batteries are achieved.
Smart Images

Figure CN119627213A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a secondary battery, in particular to a secondary battery and a device comprising the secondary battery, belonging to the field of batteries. Background Art
[0002] If new energy vehicles are to replace traditional fuel vehicles, charging speed is one of the key technologies that must be overcome. It is also a very important indicator that affects the user experience. In addition, high temperature performance (including high temperature cycle and high temperature storage) is extremely important for the user experience throughout the entire life cycle. To this end, major power battery companies have successively invested a lot of manpower and material resources. In a specific power battery system, the key to determining its charging speed is the negative electrode.
[0003] Currently, most research focuses on the design of negative electrode active materials, and very little attention is paid to the design of negative electrode plates. A large number of studies have shown that negative electrode active materials with excellent power performance may not be able to achieve the goal of continuous fast charging if unreasonable plate designs are used, while negative electrode active materials with average power performance can also achieve fast charging effects if reasonable plate designs are used. Therefore, the selection of negative electrode active materials and negative electrode plate design are the key to achieving fast charging.
[0004] The negative electrode system using pure graphite has a lower theoretical capacity (372 mAh g -1 ) cannot meet the development needs of high energy, and the development of new higher capacity negative electrode materials has become a current research hotspot. In recent years, the development of silicon-based materials such as silicon-oxygen, silicon-carbon and nano-silicon has progressed rapidly, but their actual application has encountered many problems, especially in some high-end applications (such as pure electric vehicles, smart phones, etc.).
[0005] Therefore, there is an urgent need to develop a novel secondary battery. Summary of the invention
[0006] In order to overcome the technical defect in the prior art that the fast-charging graphite negative electrode has large surface defects, making it difficult to take into account high-energy fast charging, long cycle and good high-temperature storage characteristics, the present invention provides a secondary battery and a device including the secondary battery.
[0007] A first aspect of the present invention provides a secondary battery, which includes a negative electrode plate, which includes a negative electrode collector and a negative electrode material layer arranged on at least one surface of the negative electrode collector, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes a carbon-based material, wherein the surface defect growth rate of the negative electrode plate is 5% to 25%, wherein the surface defect growth rate of the negative electrode plate = (surface defect degree of the negative electrode plate after storage - surface defect degree of the negative electrode plate after rolling) / surface defect degree of the negative electrode plate after rolling, and the surface defect degree refers to the peak area ratio of the D peak to the G peak of the carbon-based material.
[0008] A second aspect of the present invention provides a device comprising the secondary battery.
[0009] The negative electrode plate provided by the present invention has a lower surface defect degree and surface defect growth rate, which is conducive to achieving the characteristics of high-energy fast charging, long cycle and excellent high-temperature storage of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 I is the negative electrode sheet after rolling in Example 1 D / I G Distribution map of
[0011] Figure 2 I is the negative electrode plate after storage in Example 1 D / I G Distribution map of
[0012] Figure 3 I is the negative electrode plate after storage in Comparative Example 1 D / I G Distribution map of . DETAILED DESCRIPTION
[0013] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0014] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0015] A list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0016] The term "surface defect (I D / I G )” refers to the peak area ratio of the D peak to the G peak of the carbon-based material.
[0017] The term "surface defect degree of the negative electrode sheet after rolling" refers to the surface defect degree measured by placing the negative electrode sheet after rolling directly on a Raman tester at an excitation wavelength of 532 nm.
[0018] The term "surface defect degree of negative electrode sheet after storage" refers to the surface defect degree measured by charging the full battery after capacity conversion to 100% state of charge and then placing it at 45℃~85℃ for 7 days to 360 days. The full battery is disassembled and the negative electrode sheet is cleaned with DMC, and the cleaned sheet is directly placed on the Raman tester at an excitation wavelength of 532nm.
[0019] The term "surface defect growth rate" refers to (surface defect degree of the negative electrode sheet after storage - surface defect degree of the negative electrode sheet after rolling) / surface defect degree of the negative electrode sheet after rolling.
[0020] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0021] The negative electrode sheet obtained by adjusting the preparation method of the carbon-based material in the present invention has a lower surface defect degree after rolling. At the same time, after the negative electrode sheet is assembled into a battery cell and stored at a certain temperature for several days, the disassembled negative electrode sheet also shows a lower surface defect degree growth. In addition, the surface defect growth rate of the negative electrode sheet (mainly affected by the mass ratio of aggregate to asphalt in the granulation step) is 5% to 25%. When the surface defect growth rate of the negative electrode sheet is too large or too small, the rate performance and cycle performance of the lithium-ion battery are relatively poor. Based on the above improvements, the lithium-ion battery provided by the present invention also exhibits high energy density, better fast charging capability, excellent cycle stability and good high temperature storage characteristics.
[0022] In some embodiments, the surface defect growth rate of the negative electrode sheet is 5% to 20%; in some embodiments, the surface defect growth rate of the negative electrode sheet is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any range therebetween.
[0023] In some embodiments, the surface defect degree of the negative electrode sheet after rolling is 0.5 to 0.9; when the surface defect degree of the negative electrode sheet after rolling is too small, the kinetic performance is relatively poor, and the manufacturing requirements are high, which increases the manufacturing cost; when the surface defect degree of the negative electrode sheet after rolling is too large, the reaction between such defects and the electrolyte increases, resulting in side effects such as degradation of life characteristics; in some embodiments, the surface defect degree of the negative electrode sheet after rolling is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or any range therebetween.
[0024] In some embodiments, the surface defect degree of the negative electrode plate after storage is 0.5 to 1.2; when the surface defect degree of the negative electrode plate after storage is too small, the kinetic performance is relatively poor, and the manufacturing requirements are high, which increases the manufacturing cost; when the surface defect degree of the negative electrode plate after storage is too large, the reaction between such defects and the electrolyte increases, resulting in side effects, such as degradation of life characteristics; in some embodiments, the surface defect degree of the negative electrode plate after storage is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or any range therebetween; in some embodiments, the surface defect degree of the negative electrode plate after storage is 0.5 to 1.0.
[0025] In some embodiments, the carbon-based material includes at least one of graphite, soft carbon and hard carbon; in some embodiments, the Dv50 of the carbon-based material satisfies 10μm≤Dv50≤20μm; in some embodiments, the Dv50 of the carbon-based material is 10μ, 10μm, 12μm, 15μm, 17μm, 19μm, 20μm or any range therebetween.
[0026] In some embodiments, the negative electrode active material further comprises a silicon-based material; in some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material satisfies 0%≤M 硅基材料 ≤40%; in some embodiments, the graphite includes carbon-coated graphite; in some embodiments, the carbon-coated graphite includes at least one of hard carbon-coated graphite and soft carbon-coated graphite; in some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any range therebetween; in some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material satisfies 10%≤M 硅基材料 ≤30%; In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon oxides and silicon-carbon materials.
[0027] In some embodiments, based on the mass of the negative electrode material layer, the mass content of the negative electrode active material satisfies 94%≤M 负极活性材料 ≤97%; in some embodiments, based on the mass of the negative electrode material layer, the mass content of the negative electrode active material is 94%, 95%, 96%, 97% or any range therebetween.
[0028] In some embodiments, the double-sided surface density of the negative electrode plate is 15 mg / cm 2 ~25mg / cm 2 In some embodiments, the double-sided surface density of the negative electrode plate is 15 mg / cm 2 、18mg / cm 2 , 21mg / cm 2 , 23mg / cm 2 , 25mg / cm 2 Or any range therebetween; In some embodiments, the compaction density of the negative electrode sheet is 1.2 g / cm 3 ~1.8g / cm 3 In some embodiments, the compaction density of the negative electrode sheet is 1.2 g / cm 3 , 1.4g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 or any range in between.
[0029] A second aspect of the present invention provides a device comprising the secondary battery.
[0030] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium.
[0031] In some embodiments, the carbon-based material further comprises at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene. In some embodiments, the tin-based material comprises at least one of tin, tin oxide and tin alloy. In some embodiments, the phosphorus-based material comprises phosphorus and / or phosphorus complexes.
[0032] In some embodiments, the negative electrode material layer further comprises a binder and a conductive agent. In some embodiments, the binder comprises, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0033] In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material includes at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0034] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode current collector comprises: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0035] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0036] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0037] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.
[0038] In some embodiments, the present application also provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0039] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0040] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.
[0041] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0042] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0043] The shape of the secondary battery described in the present application may be cylindrical, square or any other shape, such as a square soft pack.
[0044] Examples and Comparative Examples
[0045] Example 1
[0046] (1) Preparation of positive electrode sheet:
[0047] The positive electrode active material LiNi 0.9 Co 0.03 Mn 0.07 O 2 , Super P, multi-walled carbon tubes, and PVDF are dispersed in an appropriate amount of NMP at a mass ratio of 97.5:0.9:0.5:1.1 to form a uniform positive electrode slurry. The positive electrode slurry is coated on aluminum foil, and after drying, rolling, and other processes, a positive electrode sheet is obtained.
[0048] The compaction density of the positive electrode sheet is 3.5 g / cm 3 , surface density is 25mg / cm 2 .
[0049] (2) Preparation of negative electrode sheet
[0050] Artificial graphite secondary particles and pre-lithium silicon oxide compounds (commercially available) are pre-mixed in a mass ratio of 100:25 to obtain a negative electrode active material, and the negative electrode active material is homogenized with carbon black, carbon nanotubes, CMC, SBR and PAA in a mass ratio of 96:0.9:0.1:0.6:1.2:1.2 to obtain a uniformly dispersed slurry. Finally, the slurry is coated on a 6μm copper foil, dried at 90°C, and then rolled to obtain a silicon-containing negative electrode sheet for use. The preparation of the artificial graphite secondary particles is as follows:
[0051] a) Raw material crushing: The raw coke is crushed by a mechanical mill and then classified to obtain specific aggregates, wherein the Dv50 of the aggregate is 8.0 μm and the Dv10 is 3-4 μm;
[0052] b) Aggregate shaping: The above aggregates are shaped by a shaping machine, the processing time is 30 minutes, and the rotation speed is 1500 rpm;
[0053] c) Granulation: The shaped aggregate and asphalt are mixed in a mass ratio of 100:9, added into a drum-type, horizontal or vertical reactor, heated to 600°C at a rate of 5°C / min, and reacted for 2 hours to obtain an artificial graphite secondary particle precursor A, wherein the Dv50 of the artificial graphite secondary particle precursor A is 14.5 μm;
[0054] d) Graphitization treatment: adding the artificial graphite secondary particle precursor A into a box-type or Acheson graphitization furnace, performing high-temperature graphitization treatment at 2800° C. for 20 h, and cooling to obtain an artificial graphite secondary particle precursor B;
[0055] e) Coating: The artificial graphite secondary particle precursor B and liquid asphalt are mixed in a mass ratio of 100:10, and then carbonized in a roller kiln heat treatment device, wherein the heating rate is 10°C / min, the heat treatment temperature is 1250°C, the insulation time is 2h, and the temperature is lowered to obtain artificial graphite secondary particles, wherein the Dv50 of the artificial graphite secondary particles is 13.5μm.
[0056] The double-sided surface density of the silicon-containing negative electrode obtained is 22 mg / cm 2 , compacted density is 1.65g / cm 3 .from Figure 1 It can be seen that the negative electrode sheet in Example 1 after rolling (negative electrode sheet after rolling) has an I D / I G The median value is about 0.76, and almost all I D / I G All are less than 1.6. Figure 2 It can be seen from the figure that the negative electrode sheet in Example 1 after storage (negative electrode sheet after storage) has an I D / I G The median value is about 0.83. Therefore, the surface defect growth rate of the negative electrode sheet prepared in Example 1 (i.e., the I of the negative electrode sheet after storage (before cycling)) is D / I G -I of negative electrode sheet after rolling D / I G ) / I of negative electrode sheet after rolling D / I G ) is 9.2%, that is, after the negative electrode is stored at a certain temperature for several days, its surface defect degree does not change significantly.
[0057] (3) Preparation of electrolyte:
[0058] LiPF6 was dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate (volume ratio 1:1:1), and 10 wt% of fluoroethylene carbonate was added as a film-forming additive to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0059] (4) Isolation film: polyethylene isolation film.
[0060] (5) Outer packaging: aluminum-plastic film.
[0061] (6) Preparation of lithium-ion batteries:
[0062] The positive electrode sheet, the separator, and the negative electrode sheet are wound or stacked in order to form a battery cell, and then the battery cell is placed in an outer package, injected with electrolyte and sealed to obtain the secondary battery of the present application.
[0063] Example 2
[0064] The steps of Example 2 are the same as those of Example 1, except that in Example 2, during step c) granulation, the mass ratio of aggregate to asphalt is 100:3.
[0065] The Dv50 of the artificial graphite secondary particles prepared in Example 2 is 11.8 μm.
[0066] Example 3
[0067] The steps of Example 3 are the same as those of Example 1, except that in Example 3, during step c) granulation, the mass ratio of aggregate to asphalt is 100:6.
[0068] The Dv50 of the artificial graphite secondary particles prepared in Example 3 is 12.5 μm.
[0069] Example 4
[0070] The steps of Example 4 are the same as those of Example 1, except that in Example 4, during step c) granulation, the mass ratio of aggregate to asphalt is 100:12.
[0071] The Dv50 of the artificial graphite secondary particles prepared in Example 4 is 17.8 μm.
[0072] Example 5
[0073] The steps of Example 5 are the same as those of Example 1, except that in Example 5, when preparing the negative electrode plate in step (2), no pre-lithium silicon oxide compound is added.
[0074] Example 6
[0075] The steps of Example 6 are the same as those of Example 1, except that in Example 6, during the preparation of the negative electrode plate in step (2), the mass ratio of the artificial graphite secondary particles to the pre-lithium silicon oxide compound is 100:15.
[0076] Example 7
[0077] The steps of Example 7 are the same as those of Example 1, except that in Example 7, during the preparation of the negative electrode plate in step (2), the mass ratio of the artificial graphite secondary particles to the pre-lithium silicon oxide compound is 100:35.
[0078] Example 8
[0079] The steps of Example 8 are the same as those of Example 1, except that in Example 8, when preparing the negative electrode plate in step (2), the silicon-based material is a silicon oxide compound (not pre-lithium).
[0080] Comparative Example 1
[0081] The steps of Comparative Example 1 are the same as those of Example 1, except that, in Comparative Example 1, the preparation method of artificial graphite secondary particles is as follows:
[0082] a) Raw coke crushing: The raw coke is crushed by using a jet mill, a mechanical mill or a roller mill, and then subjected to a classification process to obtain aggregates with a Dv50 of 8.0 μm and a Dv10 of 3 to 4 μm;
[0083] b) Aggregate shaping: The above aggregates are shaped by a fusion machine, the processing time is 30 minutes, and the rotation speed is 1500 rpm;
[0084] c) Graphitization treatment: Add the above-mentioned shaped aggregate into a box-type or Acheson graphitization furnace, perform high-temperature graphitization treatment at 2800°C, the heating time is 20h, and after cooling, the fast-filling graphite precursor A is obtained;
[0085] f) Coating: The above-mentioned fast-filling graphite precursor A and asphalt are mixed in a mass ratio of 100:8, and then carbonized in a heat treatment device such as a box furnace / roller kiln / rotary kiln. The heating rate is 5°C / min, the heat treatment temperature is 1200°C, and the insulation time is 2h. After cooling, fast-filling artificial graphite secondary particles are obtained, and their Dv50 is 13.5μm.
[0086] from Figure 3 It can be seen that the negative electrode sheet prepared in Comparative Example 1 has a D / I G The median value is about 1.12, the surface defect growth rate is 23.1%, and almost all I D / I G Both are greater than 0.4.
[0087] Comparative Example 2
[0088] The steps of Comparative Example 2 are the same as those of Example 1, except that in Comparative Example 2, during granulation, the mass ratio of aggregate to asphalt is 100:15.
[0089] The Dv50 of the artificial graphite secondary particles prepared in Comparative Example 2 was 19.7 μm.
[0090] Test method:
[0091] 1. Test of surface defect degree and surface defect growth rate:
[0092] The negative electrode sheet after rolling was directly placed on the Raman tester for testing, with an excitation wavelength of 532nm. The median value of the surface defect (I D / I G ) is denoted as G1;
[0093] The full battery after capacity conversion was charged to 100% state of charge and then placed at 60°C for 14 days. The full battery was disassembled and the negative electrode was cleaned with DMC. The cleaned electrode was directly placed on a Raman tester for testing with an excitation wavelength of 532nm. The median value of the surface defect (i.e., the I D / I G ) is recorded as G2.
[0094] The surface defect growth rate (i.e., the rate of change of surface defect degree after storage) is: (G2-G1) / G1×100%.
[0095] 2. Cycle performance test:
[0096] At 25°C, first charge at 1C constant current to 4.25V, then charge at constant voltage to a current of 0.05C. After standing for 10 minutes, discharge at 1C constant current to 2.5V. Perform a cycle test in this full charge and discharge form until the discharge capacity of the lithium-ion battery decays to 80% of the initial capacity, and record the number of cycles at this time.
[0097] 3. High temperature storage performance test:
[0098] The full battery after capacity division is charged to 100% state of charge in the form of 0.33C CC+CV, and the discharge capacity after capacity division is recorded as C1. After being placed at 60℃ for 14 days, the battery cell is taken out and allowed to stand at 25℃ for 4h, and then discharged to 2.5V at a rate of 0.33C, allowed to stand for 10min, and then charged to 4.25V at a rate of 0.33C, allowed to stand for 10min, and then charged at a constant voltage to a current of 0.05C, and finally discharged to 2.5V at a rate of 0.33C. The discharge capacity at this time is recorded as C2, and the recovery retention rate after storage = C2 / C1*100%.
[0099] 4. 3C / 0.33C capacity ratio determination:
[0100] At 25°C, the full battery was charged at a constant voltage to a current of 0.05C, then discharged at a rate of 0.33C to 2.5V, and activated in this way of full charge and discharge for 3 weeks, charged at a rate of 3C to 4.25V, left to stand for 10 minutes, then charged at a constant voltage to a current of 0.05C, and then discharged at a rate of 0.33C to 2.5V. The 3C / 0.33C capacity ratio = 3C constant current charging capacity / 0.33C charging total capacity in the third week. The larger the 3C / 0.33C ratio, the better its fast charging capability.
[0101] The test results are shown in Table 1
[0102] Table 1
[0103]
[0104]
[0105] As can be seen from Table 1, the negative electrode plate provided by the present invention has a lower surface defect degree and surface defect growth rate, which is conducive to achieving the high-energy fast charging, long cycle and excellent high-temperature storage characteristics of lithium-ion batteries.
[0106] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A secondary battery comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprising a negative electrode active material, the negative electrode active material comprising a carbon-based material, wherein: The surface defect growth rate of the negative electrode plate is 5% to 25%, Wherein, the surface defect growth rate of the negative electrode sheet=(surface defect degree of the negative electrode sheet after storage-surface defect degree of the negative electrode sheet after rolling) / surface defect degree of the negative electrode sheet after rolling, The surface defect degree refers to the peak area ratio of the D peak to the G peak of the carbon-based material.
2. The secondary battery according to claim 1, characterized in that: The surface defect growth rate of the negative electrode plate is 5% to 20%.
3. The secondary battery according to claim 2, characterized in that: The surface defect growth rate of the negative electrode plate is 6% to 10%.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The surface defect degree of the negative electrode sheet after rolling is 0.5 to 0.9; and / or The surface defect degree of the negative electrode plate after storage is 0.5 to 1.
2.
5. The secondary battery according to claim 4, characterized in that: The surface defect degree of the negative electrode plate after storage is 0.5 to 1.
0.
6. The secondary battery according to claim 1, characterized in that: The carbon-based material includes at least one of graphite, soft carbon and hard carbon, and / or; The Dv50 of the carbon-based material satisfies 10 μm≤Dv50≤20 μm; and / or The negative electrode active material also includes a silicon-based material.
7. The secondary battery according to claim 6, characterized in that: Based on the mass of the negative electrode active material, the mass content of the silicon-based material satisfies 0%≤M 硅基材料 ≤40%.
8. The secondary battery according to claim 6, characterized in that: The silicon-based materials include silicon, silicon alloys, silicon oxides and silicon-carbon materials; and / or Based on the mass of the negative electrode active material, the mass content of the silicon-based material satisfies 10%≤M 硅基材料 ≤30%.
9. The secondary battery according to any one of claims 1 to 3, characterized in that: Based on the mass of the negative electrode material layer, the mass content of the negative electrode active material satisfies 94%≤M 负极活性材料 ≤ 97%; and / or The double-sided surface density of the negative electrode plate is 15 mg / cm 2 ~25mg / cm 2 ; and / or The compaction density of the negative electrode sheet is 1.2 g / cm 3 ~1.8g / cm 3 .
10. A device comprising the secondary battery according to any one of claims 1 to 8.